The effect of some biofertilizers and salicylic acid on the growth and production of pepper in Greenhouses - حماد , ياسر; راعي, سليم; ابراهيم , محمد (Latakia University Journal -Biological Sciences Series, 2020)
The aim of this study was to determine the efficiency of some biological fertilizers and salicylic acid on the growth and production of pepper in greenhouse used parameters were: plant height, shoot fresh weight, root fresh weight, fruit weight expirment in tartous in 2018/2019 season. The results showed that fertilization with bio-fertilizers and salicylic acid resulted in a significant increase in all studied treatments compared to control (non-vaccinated with bacterial control and untreated with salicylic acid). The best results were observed when treating fertilization with the first bio-fertilizer (M1) with salicylic acid concentration (S3) and significant differences in plant height, fresh weight of shoot and root, and fruits weight increased by (71.39 - 177.77 - 113.41 - 220.22%) compared to the untreated control. The respectively irrigation with salicylic acid (S3) was significantly superior in plant height, fresh weight of shoot and root, and fruit weight increased by (16.38 - 45.60 - 30.48 - 50%) compared to untreated control respectively.